การเปรียบเทียบตัวแปรทางชีวกลศาสตร์ของการชกหมัดตรงระหว่างการชกด้วยท่ายืนแบบเท้านำเท้าตามและแบบเท้าขนานกันในนักมวย - ภุชงค์ ศรีเพียงจันทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
Methods: Boxers and/or Muay Thai boxers from a boxing camp in Bangkok who were between 17-25 years of age and whose body weight was between 52-64 kg were purposively selected. The participants were asked to throw straight punches with their maximum effort in four different straight punch styles, i.e., 1. Parallel foot stance without trunk rotation, 2. Lead and rear foot stance without trunk rotation, 3. Parallel foot stance with trunk rotation, and 4. Lead and rear foot stance with trunk rotation. The punching style were randomly assigned. The participants were asked to perform 5 punches in each punching style. The obtained data were analyzed in terms of mean, standard deviation, and one-way repeated measures ANOVA with post-hoc Bonferroni at the statistically significant level of p<05.Results: Punching forces were statistically different among the four punching styles (p<.05). The order of the punching forces were 1. Lead and rear foot stance with trunk rotation, 2. Parallel foot stance with trunk rotation, 3. Lead and rear foot stance without trunk rotation, and 4. Parallel foot stance without trunk rotation. As a result, trunk rotation played critical role in creating punching force in straight punch.Conclusion: Throwing a powerful straight punch follows the concept of kinetic chain where punching force is first developed from the ankle before transferring through joints, knee, hip, shoulder, elbow, hands, and finally to punching forces. To transfer force from the lower extremity to the upper extremity, pelvic and trunk rotations are critical mechanisms.